Analisis Pengaruh Kualitas Institusi Politik terhadap Konsentrasi PM2.5 di Negara G20 - Pratama, Afif Dhia; Rahmayani, Dwi (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study aims to analyze the influence of political institutional quality, proxied by democracy, political globalization, and good governance, on PM2.5 concentration in G20 countries as well as prove the Environmental Kuznets Curve (EKC) Hypothesis and Pollution Halo Hypothesis (PHH) from 1998 to 2022. The Autoregressive Distributed Lag (ARDL) method is employed in this analysis. The results show that democracy reduces PM2.5 concentration only in the long run. However, good governance decreases PM2.5 concentration in the short term but increases it in the long run. Political globalization shows no significant influence on PM2.5 concentration. Furthermore, the study also revealed that the EKC hypothesis is proven, but the PHH is not proven.